PENGGUNAAN MEDIA PEMBELAJARAN WEB TERHADAP KETERAMPILAN MENULIS PADA MATA PELAJARAN BAHASA INDONESIA KELAS V SDIT AL-FURQAN PALANGKA RAYA - Nanda Sabila; Mila; Sulistyowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to see the differences in the use of web learning media on writing skills in Indonesian language subjects, especially in the aspect of capital letter writing in fifth grade students of SDIT Al-Furqan Palangka Raya. A quantitative approach was employed using a one-group pretest-posttest research design. The participants consisted of 18 fifth-grade students from the Abu Hanifah. Data were gathered through observation checklist, documentation, and performance asessment sheets to evaluate students' writing abilities, and were subsequently analyzed using a paired sample t-test. Observations findings indicated that f teacher and student activities reached average percentages of 99% and 92% both caregorized as very good. Students' writing skills improved from average pretest score of 56 to an average posttest score of 76 and the results of the study showed a t-count value of -6.398 with a significance value (2-tailed) = 0.001 <0.05. This shows that there is a significant difference in the use of web learning media on writing skills in fifth grade Indonesian language subjects at SDIT Al-Furqan Palangka Raya.